2010
DOI: 10.4049/jimmunol.0904133
|View full text |Cite
|
Sign up to set email alerts
|

Human Neuronal Cells Possess Functional Cytoplasmic and TLR-Mediated Innate Immune Pathways Influenced by Phosphatidylinositol-3 Kinase Signaling

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 80 publications
(117 reference statements)
4
96
0
Order By: Relevance
“…Another possibility is that TLRs might induce post-SCI NLRP1 inflammasome formation. Although TLRs are generally considered to be expressed in microglia and astrocytes, recent research has showed that TLR expression in neurons is pivotal under both physiological and pathological conditions [54][55][56][57]. Perhaps SCI changes expression of certain TLRs which recognize danger signals after injury and subsequently causes inflammasome formation.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that TLRs might induce post-SCI NLRP1 inflammasome formation. Although TLRs are generally considered to be expressed in microglia and astrocytes, recent research has showed that TLR expression in neurons is pivotal under both physiological and pathological conditions [54][55][56][57]. Perhaps SCI changes expression of certain TLRs which recognize danger signals after injury and subsequently causes inflammasome formation.…”
Section: Discussionmentioning
confidence: 99%
“…The TC-83 vaccine strain of VEEV was obtained from Robert Tesh (University of Texas Medical Branch, Galveston, TX), and the New Guinea C and H241 strains of DENV-2 and DENV-4, respectively, were obtained from Sonja Gerrard (University of Michigan, Ann Arbor, MI). Green fluorescent protein (GFP)-tagged Sendai virus (GFP-SeV) was obtained from Valery Grdzelishvili (University of North Carolina at Charlotte, Charlotte, NC) and has been previously described (24).…”
Section: Methodsmentioning
confidence: 99%
“…WEEV replicon assays used BSR-T7 cells and pWR-LUC, pW-nsP, or pWR-⌬LUC and measured fLUC accumulation as a surrogate marker for viral RNA replication as previously described (13,19). GFP-SeV replication was determined by fluorescence accumulation as previously described (24). Quantitative reverse-transcription (RT)-PCR was done as previously described (19,24,25), where threshold cycle (⌬⌬C T ) values were calculated to determine relative RNA levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRRs are abundantly expressed in both neuronal and non-neuronal cells including the immune cells (e.g. monocytes, macrophages, dendritic cells and other immunerelated cells such as keratinocytes) (82,83). Other types of PRRs include RIG-like helicases (RLHs), C-type lectins (CTLs) and the recently discovered, Nod-like receptors (NLRs) (84).…”
Section: Intracellular Signals In Inflammationmentioning
confidence: 99%